The Devastating Psychological Impact on Elementary School Students of Bullying in Indonesia: Dampak Psikologis yang Menghancurkan pada Siswa Sekolah Dasar Akibat Perundungan di Indonesia - Salsadila Elsa Nugroho; Nurul Azizah (Academia Open, 2024)
This study examines bullying at Larangan Sidoarjo Public Elementary School in South Sidoarjo and its psychological effects on victims. Using a qualitative case study method, data were collected through interviews and observations with teachers, parents, and victims, supplemented by secondary sources. Analysis followed the Miles and Huberman approach. Findings indicate that bullying includes both physical and verbal forms, leading to psychological issues such as low self-confidence, environmental anxiety, trauma in forming new friendships, and communication embarrassment. One notable case involved a student, RDF, who became introverted and sad due to verbal bullying about physical differences. The study underscores the need for effective anti-bullying programs and psychological support in schools. Highlights: 1. Bullying Types: Physical and verbal forms identified.2. Psychological Impact: Low self-confidence, anxiety, trauma in friendships.3. Case Highlight: RDF became introverted from verbal bullying about physical differences. Keywords: Bullying, Psychological effects, Elementary school, Qualitative study, Anti-bullying programs